Mechanical and natural ventilation systems in a greenhouse designed using computational fluid dynamics - Flores-Velazquez, Jorge; Montero, Juan I.; Baeza, Esteban J.; Lopez, Juan C. (International Journal of Agricultural and Biological Engineering, 2014)
The aim of this study was to analyse air exchange and temperature distribution in a greenhouse with combined mechanical and natural ventilation and to design more efficient mechanical ventilation systems. For this purpose, a computational fluid dynamics (CFD) model of the greenhouse was used. Three configurations were considered: Configuration 1 (mechanical ventilation and closed roof ventilators), Configurations 2 and 3 (mechanical ventilation and roof ventilators open 30% and 100%, respectively). After validation, the CFD model was used to improve the design of the greenhouse mechanical ventilation system in each of the three configurations analyzed. Four greenhouse lengths, 28 m, 50 m, 75 m and 100 m, were used in the simulations. Compared to fan ventilation only, roof ventilation improved the climate of fan-ventilated greenhouses in terms of the air exchange rate (22%) and climate uniformity because the internal air was mixed better than with mechanical ventilation only. As the greenhouse length increased, more advantages were achieved with natural ventilation compared to mechanical ventilation. For most configurations, there was a strong linear correlation between temperature gradient and greenhouse length. The greenhouse whose regression line had the steepest slope was the one with closed roof ventilators. Increasing the fan capacity produced a general reduction in temperature, but the effect was less intense for the greenhouses with open roof ventilators. Compared to box inlet ventilators, an enlarged continuous inlet in the wall opposite the fans increased overall system performance because it eliminated backflow recirculation zones, which are prone to produce high temperatures.